2020
DOI: 10.3390/jof6020091
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Associated Pulmonary Aspergillosis (CAPA)—From Immunology to Treatment

Abstract: Like severe influenza, coronavirus disease-19 (COVID-19) resulting in acute respiratory distress syndrome (ARDS) has emerged as an important disease that predisposes patients to secondary pulmonary aspergillosis, with 35 cases of COVID-19 associated pulmonary aspergillosis (CAPA) published until June 2020. The release of danger-associated molecular patterns during severe COVID-19 results in both pulmonary epithelial damage and inflammatory disease, which are predisposing risk factors for pulmonary aspergillosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
404
3
14

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(452 citation statements)
references
References 104 publications
(167 reference statements)
8
404
3
14
Order By: Relevance
“…Second, type-2 diabetes, which remains a major comorbidity for severe COVID-19 [10,27] and increases the risk of mortality, especially in individuals with poorly controlled blood glucose [28]. Third, superinfection, which represents a new albeit scarcely studied condition in COVID-19 [5], particularly for invasive fungal infections [14,29]. The peculiar pathophysiology of either diabetes [11] or COVID-19 [30] may account for the occurrence of bacterial and fungal coinfections in our case, as in other cases [3,31].…”
Section: Discussionmentioning
confidence: 99%
“…Second, type-2 diabetes, which remains a major comorbidity for severe COVID-19 [10,27] and increases the risk of mortality, especially in individuals with poorly controlled blood glucose [28]. Third, superinfection, which represents a new albeit scarcely studied condition in COVID-19 [5], particularly for invasive fungal infections [14,29]. The peculiar pathophysiology of either diabetes [11] or COVID-19 [30] may account for the occurrence of bacterial and fungal coinfections in our case, as in other cases [3,31].…”
Section: Discussionmentioning
confidence: 99%
“…More than 30 cases of COVID-19-associated pulmonary aspergillosis (CAPA) have been published to date [9]. Overall, the possible development of invasive pulmonary aspergillosis in some critically ill COVID-19 patients is somewhat expected, considering the following, likely cumulative risk factors: (1) the epithelial lung damage caused by either the virus or the dysregulated host response; (2) the frequent use of corticosteroids [10]; (3) a possible similarity with influenza-associated invasive aspergillosis (IAPA) [11].…”
Section: Covid-19-associated Pulmonary Aspergillosismentioning
confidence: 99%
“…Since late 2019, a novel betacoronavirus (SARS-CoV-2) has rapidly spread around the world, causing a global pandemic of coronavirus-19 disease (COVID-19) with over 13 million cases and in excess of 500 000 deaths to date (14 th July 2020). The disease spectrum in COVID-19 ranges from asymptomatic infection to severe illness with acute respiratory distress syndrome (ARDS) requiring critical care, with 20-40% of hospitalised symptomatic patients developing ARDS (10)(11)(12). An increasing number of anecdotal case reports and case series have identified COVID-19 associated pulmonary aspergillosis (CAPA) as an additional infective complication of COVID-19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Downloaded Frommentioning
confidence: 99%
“…The disease spectrum in COVID-19 ranges from asymptomatic infection to severe illness with acute respiratory distress syndrome (ARDS) requiring critical care, with 20-40% of hospitalised symptomatic patients developing ARDS (10)(11)(12). An increasing number of anecdotal case reports and case series have identified COVID-19 associated pulmonary aspergillosis (CAPA) as an additional infective complication of COVID-19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). Depending on the study and the region of origin, reported incidence rates for CAPA ranged from approximately 5% (14) to 20-35% (17)(18)(19)(20)(21).…”
Section: Downloaded Frommentioning
confidence: 99%
See 1 more Smart Citation